1999
DOI: 10.1038/sj.bmt.1701635
|View full text |Cite
|
Sign up to set email alerts
|

Three AML patients with existing or pre-existing intracerebral granulocytic sarcomas who were successfully treated with allogeneic bone marrow transplantations

Abstract: Summary:We report three acute myelogenous leukemia (AML) patients who developed intracerebral granulocytic sarcomas (GS) and were successfully treated with allogeneic BMT (allo-BMT). The diagnosis of one patient was AML M2 with myelofibrosis, and the other two patients were AML M4 with eosinophilia (AML M4 Eo), according to the FAB classification. Two patients first experienced a relapse in the brain that resulted in the formation of GS, followed by a relapse in the bone marrow. The remaining patient developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Stem cell transplantation may improve survival by virtue of the high dose chemotherapy and total body irradiation regimens employed. Several authors have reported allogeneic stem cell transplantation to be part of successful treatment [19,20]. This may be attributable not only to the high dose conditioning therapy but also to the graft-versus-leukemia (GVL) effect associated with allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell transplantation may improve survival by virtue of the high dose chemotherapy and total body irradiation regimens employed. Several authors have reported allogeneic stem cell transplantation to be part of successful treatment [19,20]. This may be attributable not only to the high dose conditioning therapy but also to the graft-versus-leukemia (GVL) effect associated with allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 Tallman et al 4 reported one case with persistent orbital GS and multiple GS in the right lung who was successfully treated with allo-BMT. Kowal-Vern et al 8 presented a case with GS of the ileum that was also successfully treated with surgical excision of the primary tumor and allo-BMT.…”
Section: Discussionmentioning
confidence: 99%